Pengembangan Media Pembelajaran Berbasis Android pada Mata Kuliah Mesin-Mesin Listrik - Nofrida Yanti; Hansi Effendi (Jurnal Pendidikan Teknik Elektro, 2022)
The problem in this exploration is the appropriate and fluctuating learning media at Padang State University, with the right student learning outcomes. This study aims to disseminate learning media and form substantial, functional, and interesting media in electronic engineering courses for students majoring in electrical engineering, Padang State University. This study uses Research and Development (R&D) planning, using a 4-D improvement model. 4-D repair techniques are Define, Design, Development and Disseminate. The information evaluation method used is intended to describe the truth and reasonable reasoning behind the educational media. the result obtained from this development research is an Android-oriented learning media. Judging from the consequences of this exploration, it can be said that the media designed is declared valid, from the point of view of using the material from a practical point of view. Media designed very simply for students. Finally, the Android-based learning media designed can be used and easy to develop student learning outcomes.